An environmentally friendly anti-interference control cable and its preparation method
By using a tinned copper wire braided shielding layer and a polyvinyl chloride composite outer sheath in the anti-interference control cable, combined with modified glass fiber and perlite powder, the problem of mechanical damage to the cable outdoors is solved, and the durability and safety of the cable are improved.
Patent Information
- Application Number
- CN202510342324.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2045-03-21
AI Technical Summary
Existing anti-interference control cables are susceptible to mechanical damage during outdoor use, resulting in exposed conductors, causing short circuits and safety issues.
The shielding layer woven with tinned copper wire and the outer sheath made of polyvinyl chloride composition, combined with modified glass fiber, modified perlite powder and other materials, improve the mechanical strength and wear resistance of the cable and enhance the cable's ability to resist external damage.
It effectively prevents cables from being damaged by mechanical damage in outdoor environments, prolongs the service life of cables, and improves the electrical safety and structural stability of cables.
Smart Images

Figure BDA0005323544800000101 
Figure BDA0005323544800000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cables, and more specifically, to an environmentally friendly anti-interference control cable and a preparation method thereof. Background Art
[0002] A cable is a wire used to transmit power, signals, or information. It consists of one or more insulated conductors, typically encased in a protective sheath. Cables can be categorized into various types based on their purpose and design, including power cables, communication cables, control cables, coaxial cables, and fiber optic cables. Cables play a key role in power systems, communication networks, building wiring, industrial automation, transportation, and the military, and are a vital component of modern infrastructure.
[0003] Interference-resistant control cables are specifically designed to provide stable signal transmission in environments with electromagnetic interference (EMI) and radio frequency interference (RFI). They employ various interference-resistant technologies, such as shielding, twisting, and isolation, to minimize the impact of external interference on signal transmission. The main components of interference-resistant control cables include a conductor, insulation, shielding, and a jacket. The outer jacket provides additional mechanical protection against physical damage and offers environmental protection, such as resistance to water, oil, and chemicals.
[0004] However, in the existing technology, anti-interference control cables working outdoors for a long time may suffer from external mechanical damage, such as being crushed by heavy objects or accidentally damaged by tools. These damages may cause the conductors of the cables to be exposed, causing safety problems such as short circuits and electric shocks. Summary of the Invention
[0005] In order to improve the problem of environmentally friendly anti-interference control cables being damaged by external mechanical damage, the present application provides an environmentally friendly anti-interference control cable and a preparation method thereof.
[0006] In a first aspect, the present application provides an environmentally friendly anti-interference control cable, which adopts the following technical solution:
[0007] An environmentally friendly anti-interference control cable comprises a conductor, an insulating layer, a shielding layer and an outer sheath, characterized in that the shielding layer is woven from tinned copper wire, and the outer sheath is made of a polyvinyl chloride composition, which comprises the following raw materials, in parts by weight: 30-36 parts of polyvinyl chloride, 20-25 parts of polypropylene, 1-2 parts of stearic acid monoglyceride, 10-13 parts of nitrile rubber, 22-25 parts of modified glass fiber, 4-6 parts of propylene glycol adipate polyester, 18-22 parts of modified perlite powder, 2-4 parts of magnesium oxide, 1-3 parts of calcium zinc stabilizer, 4-8 parts of stearic acid, 2-3 parts of antioxidant, and 1-2 parts of plasticizer.
[0008] By adopting this technical solution, the shielding layer is woven from tinned copper wire, effectively reflecting and absorbing external electromagnetic waves, reducing the impact of electromagnetic interference on the cable's internal signals. The outer sheath is made of a polyvinyl chloride composition. Polyvinyl chloride has excellent insulation properties, weather resistance, and chemical resistance. It can effectively isolate current, resist ultraviolet rays, and resist acid and alkali corrosion, preventing short circuits between the cable's internal conductors, making it suitable for outdoor and harsh environments. Polypropylene has excellent mechanical strength, toughness, and chemical resistance, providing physical protection for the cable, preventing external mechanical damage and extending its service life.
[0009] Stearic acid monoglyceride has excellent lubricating properties, improving the fluidity of the system and the compatibility between the different components in the cable material. It can reduce friction during the extrusion and stretching process of the cable material and protect the cable material from damage. Nitrile rubber has excellent oil resistance, chemical resistance, heat resistance, weather resistance, high mechanical strength and wear resistance, and can withstand the mechanical stress of the cable during use, improving the durability and service life of the cable. Modified glass fiber has extremely high strength, heat resistance, and corrosion resistance. Added to the cable sheath, it improves the mechanical strength of the cable, making it more durable, able to withstand greater tension and pressure, resist corrosion from acids, alkalis, and solvents, and withstand high operating temperatures. It reduces deformation of the cable during bending and stretching and maintains the cable's structural stability.
[0010] Propylene glycol adipate polyester has excellent electrical insulation properties and can effectively isolate current. Magnesium oxide has excellent insulation properties and can withstand high voltages. Together with propylene glycol adipate polyester, they ensure the electrical safety of the cable during use. Modified perlite powder is lightweight and porous, and can fill the gaps in the cable, providing support and protection, preventing deformation of the cable's internal structure due to external pressure. Modified perlite powder can also be loaded onto the surface and pores of modified glass fiber, increasing the strength and toughness of the modified glass fiber and subsequently improving the corresponding properties of the outer sheath. Calcium zinc stabilizer improves the thermal stability of the system, preventing decomposition due to high temperatures during processing and use. Stearic acid provides lubrication and stabilization, reducing friction in the cable material during processing.
[0011] Antioxidants prevent material aging and extend service life. Plasticizers lower the system's glass transition temperature, maintaining cable flexibility and bendability in low-temperature environments and reducing material embrittlement and breakage caused by low temperatures. The various components in the system work together to improve the strength, wear resistance, and flexibility of the cable's outer sheath, thereby extending the cable's service life.
[0012] Optionally, the conductor is made of copper wire, and the insulation layer is made of environmentally friendly polyolefin material.
[0013] By adopting the above technical solution, the insulation layer adopts environmentally friendly polyolefin material, which meets environmental protection requirements. The environmentally friendly polyolefin material has good chemical corrosion resistance, heat resistance, flame retardancy, cold resistance, flexibility and processability, and can resist the erosion of various chemical substances and extend the service life of the cable. The polyolefin material also has excellent dielectric properties and insulation properties, can effectively isolate current, and ensure the electrical safety and stability of the cable during use.
[0014] Optionally, the method for preparing the modified glass fiber comprises the following steps:
[0015] (1) placing the glass fiber in hydrogen peroxide, soaking for 10-15 minutes, washing with water, and then dispersing it in deionized water, adding polyethyleneimine, stirring for 30-35 minutes, filtering, and drying to obtain pretreated glass fiber;
[0016] (2) dispersing nano-silica in deionized water, adding sodium hydroxide, stirring for 1-1.5 hours, filtering, and drying to obtain pretreated nano-silica;
[0017] (3) Dispersing the pretreated glass fiber of step (1) in deionized water, adding the pretreated nano-silica and modified chitosan of step (2), stirring at a temperature of 80-85° C. for 1-2 h, filtering, and drying to obtain modified glass fiber.
[0018] By adopting the above technical solution, hydrogen peroxide cleans the surface of the glass fiber, removes impurities such as grease and dust, and improves the bonding performance between the glass fiber and other components. Polyethyleneimine can be loaded on the surface of the glass fiber to improve the interfacial bonding strength between the glass fiber and other components, thereby subsequently improving the overall performance of the composite material.
[0019] Nano-silica has a high specific surface area, high porosity, good dispersibility and chemical stability. Sodium hydroxide activates the surface of nano-silica, increases its surface active sites, and improves its dispersibility in composite materials and its compatibility with the matrix, hydrophilicity and interfacial bonding strength.
[0020] Pretreated glass fiber, pretreated nano-silica and modified chitosan are mixed. The pretreated nano-silica can be loaded on the surface and pores of the pretreated glass fiber, thereby increasing the strength, stiffness and impact resistance of the glass fiber, improving the wear resistance and scratch resistance of the glass fiber, and extending the service life of the material. The modified chitosan has a certain viscosity, which allows the nano-silica to adhere stably to the surface of the glass fiber, making the performance of the modified glass fiber stable. Moreover, the modified chitosan increases the interfacial bonding force of the modified glass fiber, which helps to mix evenly with other components in the cable in the future, thereby improving the comprehensive performance of the cable.
[0021] Optionally, the mass ratio of the glass fiber, nano-silica, and modified chitosan is 1:0.6-0.7:0.3-0.4.
[0022] By adopting the above technical solution, the mass ratio of glass fiber, nano-silica and modified chitosan is further limited within a certain range, thereby improving the strength, toughness and other mechanical properties and wear resistance of the glass fiber. Nano-silica can be loaded on the surface and pores of the glass fiber, thereby increasing the strength, stiffness and impact resistance of the glass fiber, and improving the wear resistance and scratch resistance of the glass fiber. Modified chitosan makes the nano-silica and glass fiber bond tightly, thereby increasing the performance stability of the modified glass fiber. The combination of glass fiber, nano-silica and modified chitosan has a synergistic effect, thereby improving the mechanical properties and wear resistance of the glass fiber, and can be subsequently used in cables to improve the comprehensive performance of the cables.
[0023] Optionally, the preparation method of the modified chitosan comprises the following steps: dispersing chitosan in deionized water, adding ammonia water, stirring evenly, washing, and drying to obtain pretreated chitosan, dispersing the pretreated chitosan in deionized water, adding nano-calcium carbonate and gum arabic, stirring at a temperature of 90-95°C for 1-2 hours, and drying to obtain modified chitosan.
[0024] By adopting the above technical solution, ammonia water can provide an alkaline environment, protonating the amino groups of chitosan, thereby dissolving it in water and forming a transparent chitosan solution. This improves the solubility of chitosan and facilitates the subsequent mixing of chitosan with other components. The pretreated chitosan is dispersed in deionized water, and nano-calcium carbonate and gum arabic are added. The nano-calcium carbonate is dispersed in the chitosan system, improving the mechanical strength and toughness of the chitosan system. The gum arabic and chitosan rely on intermolecular non-covalent interactions to cross-link, improving the biocompatibility, stability, and viscosity of chitosan. This allows the nano-calcium carbonate to be stably mixed in the system, improving the viscosity and mechanical properties of chitosan, and facilitating the subsequent modification of glass fiber.
[0025] Optionally, the mass ratio of the chitosan, nano-calcium carbonate and gum arabic is 1:0.2-0.4:0.08-0.09.
[0026] By adopting the above technical solution, the mass ratio of chitosan, nano-calcium carbonate and gum arabic is further limited within a certain range, thereby improving the viscosity and mechanical properties of chitosan. Chitosan, nano-calcium carbonate and gum arabic have a synergistic effect. Nano-calcium carbonate is dispersed in the chitosan system, which improves the mechanical strength and toughness of the chitosan system. Gum arabic and chitosan rely on non-covalent interactions between molecules for cross-linking, thereby improving the biocompatibility, stability and viscosity of chitosan, and subsequently improving the performance of glass fiber mixed with other components.
[0027] Optionally, the method for preparing the modified pearlite powder comprises the following steps:
[0028] (1) crushing the perlite, dispersing it in a sodium hydroxide solution, washing it with water, and then dispersing it in deionized water, adding nonylphenol polyoxyethylene ether, stirring it evenly, filtering it, and drying it to obtain pretreated perlite;
[0029] (2) dispersing the metal organic framework material (MOFs) in hydrochloric acid, stirring uniformly, washing with water, and then dispersing it in deionized water, adding modified carboxymethyl cellulose, stirring uniformly, filtering, and drying to obtain a pretreated metal organic framework material;
[0030] (3) Dispersing the perlite pretreated in step (1) in deionized water, adding the metal organic framework material pretreated in step (2), stirring at a temperature of 70-75° C. for 2-3 hours, and drying to obtain modified perlite powder.
[0031] By adopting the above technical solution, sodium hydroxide is used to treat the surface of the perlite to remove impurities on the surface of the perlite, thereby increasing the porosity and specific surface area of the perlite. Nonylphenol polyoxyethylene ether improves the dispersibility of the perlite in the system, reduces the viscosity of the system, and increases the fluidity, which facilitates subsequent uniform mixing with other components.
[0032] The metal organic framework material has a high specific surface area and an adjustable pore structure. The metal organic framework material is treated with hydrochloric acid to remove organic impurities and increase the specific surface area of the metal organic framework material. Modified carboxymethyl cellulose is added. The modified carboxymethyl cellulose can adhere to the surface of the metal organic framework material, thereby improving the adsorption and dispersibility of the metal organic framework material, which is helpful for subsequent mixing with perlite.
[0033] The pretreated perlite has good dispersibility, insulation and fire resistance. The pretreated metal organic framework material has excellent thermal stability, flame retardancy, mechanical strength and toughness. It can be loaded on the surface and pores of the perlite, increasing the mechanical strength and toughness of the perlite. The modified carboxymethyl cellulose has a certain viscosity, which allows the metal organic framework material to adhere to the surface and pores of the perlite, making the modified perlite have better comprehensive performance, which helps to subsequently improve the mechanical properties of the cable.
[0034] Optionally, the mass ratio of the perlite, the metal organic framework material, and the modified carboxymethyl cellulose is 1:0.6-0.8:0.3-0.5.
[0035] By adopting the above technical solution, the mass ratio of perlite, metal-organic framework material and modified carboxymethyl cellulose is further limited within a certain range, thereby improving the mechanical strength and wear resistance of the perlite. The metal-organic framework material has good mechanical properties and can be loaded on the surface and pores of the perlite, thereby increasing the mechanical properties and wear resistance of the perlite. The modified carboxymethyl cellulose has a certain viscosity, which can enable the metal-organic framework material to adhere to the surface and pores of the perlite, thereby making the modified perlite have good mechanical properties and wear resistance, which can be subsequently used in cables to improve the corresponding performance of the cables.
[0036] Preferably, the preparation method of the modified carboxymethyl cellulose comprises the following steps: dispersing carboxymethyl cellulose and acrylic acid in deionized water, stirring at a temperature of 70-75° C. for 5-8 minutes, adding Tween-80, stirring for 1-2 hours, and allowing to stand to obtain modified carboxymethyl cellulose.
[0037] By adopting this technical solution, carboxymethyl cellulose exhibits excellent thickening and stabilizing properties, forming a stable emulsion. Acrylic acid, with its excellent film-forming, adhesive, and dispersing properties, improves the system's bonding strength, stability, and dispersibility when mixed with carboxymethyl cellulose. Tween-80, a nonionic surfactant, acts as an emulsifier and dispersant, enhancing the system's emulsification and dispersibility, giving the carboxymethyl cellulose system improved viscosity, which helps improve the corresponding properties of the perlite in the subsequent process.
[0038] In a second aspect, the present application provides a method for preparing an environmentally friendly anti-interference control cable, comprising the following steps: (1) twisting high-conductivity copper wires to form a conductor;
[0039] (2) Extruding an environmentally friendly polyolefin material on the outside of the conductor to form an insulating layer;
[0040] (3) Weave tinned copper wire outside the insulation layer to form a shielding layer;
[0041] (4) extruding a polyvinyl chloride composition outside the shielding layer to form an outer protective layer;
[0042] The preparation method of the polyvinyl chloride composition comprises the following steps: uniformly mixing polyvinyl chloride, polypropylene, stearic acid monoglyceride, nitrile rubber, modified glass fiber, propylene glycol adipate polyester, modified perlite powder, magnesium oxide, calcium zinc stabilizer, stearic acid, antioxidant, and plasticizer at a temperature of 80-85° C. to obtain the polyvinyl chloride composition.
[0043] By adopting the above technical solution, the anti-interference control cable prepared by this method has good comprehensive performance and improves the service life of the cable.
[0044] In summary, this application has the following beneficial effects:
[0045] 1. The polyvinyl chloride (PVC) in this application has excellent insulation, weather resistance, and chemical resistance. It can effectively isolate current, resist ultraviolet rays, and resist acid and alkali corrosion, preventing short circuits between internal conductors of the cable, making it suitable for outdoor and harsh environments. Polypropylene has excellent mechanical strength, toughness, and chemical resistance, providing physical protection for the cable, preventing external mechanical damage and extending the cable's service life.
[0046] 2. The modified glass fiber in this application has extremely high strength, heat resistance, and corrosion resistance. It is added to the sheath of the cable to improve the mechanical strength of the cable, making it more durable, able to withstand greater tension and pressure, and able to resist the erosion of acids, alkalis, and solvents. It can withstand higher operating temperatures, reduce the deformation of the cable during bending and stretching, and maintain the structural stability of the cable.
[0047] 3. The modified perlite powder in this application can also be loaded onto the surface and pores of the modified glass fiber, increasing the strength and toughness of the modified glass fiber and subsequently improving the corresponding properties of the outer sheath. The calcium zinc stabilizer improves the thermal stability of the system, preventing decomposition due to high temperatures during processing and use. Stearic acid provides lubrication and stabilization, reducing friction in the cable material during processing. DETAILED DESCRIPTION
[0048] Preparation example of modified glass fiber
[0049] Preparation Example 1-1
[0050] The preparation method of modified glass fiber comprises the following steps:
[0051] (1) 1.6 kg of glass fiber was placed in 2 L of 6% hydrogen peroxide, soaked for 15 min, washed with water, and then dispersed in 2.2 L of deionized water. 0.3 kg of polyethyleneimine was added and stirred for 35 min. The mixture was filtered and dried to obtain pretreated glass fiber.
[0052] (2) dispersing nano-silica in 2 L of deionized water, adding 0.5 kg of sodium hydroxide, stirring for 1.5 h, filtering, and drying to obtain pretreated nano-silica;
[0053] (3) Dispersing the pretreated glass fiber of step (1) in 6 L of deionized water, adding the pretreated nano-silica and modified chitosan of step (2), stirring at a temperature of 85° C. for 2 h, filtering, and drying to obtain modified glass fiber.
[0054] The mass ratio of glass fiber, nano-silica and modified chitosan is 1:0.6:0.4.
[0055] The preparation method of modified chitosan comprises the following steps: dispersing 1 kg of chitosan in 1.5 L of deionized water, adding 0.2 L of ammonia water, stirring evenly, washing, and drying to obtain pretreated chitosan; dispersing the pretreated chitosan in 1.5 L of deionized water, adding nano-calcium carbonate and gum arabic, stirring at a temperature of 90-95° C. for 1-2 hours, and drying to obtain modified chitosan.
[0056] The mass ratio of chitosan, nano-calcium carbonate and gum arabic is 1:0.2:0.09.
[0057] Preparation Example 1-2
[0058] The difference from Preparation Example 1-1 is that in step (2), no nano-silica is added.
[0059] Preparation Examples 1-3
[0060] The difference from Preparation Example 1-1 is that in step (3), modified chitosan is not added.
[0061] Preparation Examples 1-4
[0062] The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, nano-silica and modified chitosan is 1:0.7:0.3.
[0063] Preparation Examples 1-5
[0064] The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, nano-silica and modified chitosan is 1:0.1:0.6.
[0065] Preparation Examples 1-6
[0066] The difference from Preparation Example 1-1 is that the preparation method of the modified chitosan does not add nano-calcium carbonate.
[0067] Preparation Examples 1-7
[0068] The difference from Preparation Example 1-1 is that gum arabic is not added in the preparation method of the modified chitosan.
[0069] Preparation Examples 1-8
[0070] The difference from Preparation Example 1-1 is that the mass ratio of chitosan, nano-calcium carbonate and gum arabic is 1:0.4:0.08.
[0071] Preparation Examples 1-9
[0072] The difference from Preparation Example 1-1 is that the mass ratio of chitosan, nano-calcium carbonate and gum arabic is 1:0.1:0.13.
[0073] Preparation example of modified pearlite powder
[0074] Preparation Example 2-1
[0075] The preparation method of modified pearlite powder comprises the following steps:
[0076] (1) 2 kg of perlite was crushed, dispersed in 2.5 L of 20% sodium hydroxide solution, washed with water, and then dispersed in 3 L of deionized water. 0.3 L of nonylphenol polyoxyethylene ether was added, stirred evenly, filtered, and dried to obtain pretreated perlite; (2) Metal organic framework materials (MOFs) were dispersed in 2 L of 30% hydrochloric acid, stirred evenly, washed with water, and then dispersed in 2 L of deionized water. Modified carboxymethyl cellulose was added, stirred evenly, filtered, and dried to obtain pretreated metal organic framework materials; the metal organic framework material (MOFs) was ZIF-8, purchased from Xi'an Qiyue Biotechnology Co., Ltd.; (3) The perlite pretreated in step (1) was dispersed in 8 L of deionized water, the metal organic framework material pretreated in step (2) was added, stirred at a temperature of 75°C for 3 h, and dried to obtain modified perlite powder.
[0077] The mass ratio of perlite, metal organic framework material and modified carboxymethyl cellulose is 1:0.6:0.5.
[0078] The preparation method of modified carboxymethyl cellulose comprises the following steps: dispersing 1.5 kg of carboxymethyl cellulose and 0.4 L of acrylic acid in 2.5 L of deionized water, stirring at 75° C. for 8 minutes, adding 0.3 L of Tween-80, stirring for 2 hours, and allowing to stand to obtain modified carboxymethyl cellulose.
[0079] Preparation Example 2-2
[0080] The difference from Preparation Example 2-1 is that in step (2), no metal organic framework material (MOFs) is added.
[0081] Preparation Example 2-3
[0082] The difference from Preparation Example 2-1 is that in step (2), modified carboxymethyl cellulose is not added.
[0083] Preparation Example 2-4
[0084] The difference from Preparation Example 2-1 is that the mass ratio of perlite, metal organic framework material and modified carboxymethyl cellulose is 1:0.8:0.3.
[0085] Preparation Example 2-5
[0086] The difference from Preparation Example 2-1 is that the mass ratio of perlite, metal organic framework material and modified carboxymethyl cellulose is 1:0.2:0.8.
[0087] Preparation Example 2-6
[0088] The difference from Preparation Example 2-1 is that acrylic acid is not added in the preparation method of modified carboxymethyl cellulose.
[0089] Preparation Example 2-7
[0090] The difference from Preparation Example 2-1 is that Tween-80 is not added in the preparation method of modified carboxymethyl cellulose.
[0091] Example
[0092] Example 1
[0093] An environmentally friendly anti-interference control cable comprises a conductor, an insulating layer, a shielding layer and an outer sheath, wherein the shielding layer is woven from tinned copper wire, and the outer sheath is made of a polyvinyl chloride composition, which comprises the following raw materials by weight: 36 kg of polyvinyl chloride, 20 kg of polypropylene, 1 kg of stearic acid monoglyceride, 13 kg of nitrile rubber, 25 kg of modified glass fiber, 4 kg of propylene glycol adipate polyester, 18 kg of modified perlite powder, 2 kg of magnesium oxide, 1 kg of calcium zinc stabilizer, 4 kg of stearic acid, 2 kg of antioxidant 1076, and 1 kg of plasticizer; the plasticizer is dioctyl sebacate.
[0094] The conductor is made of high-conductivity copper wire, and the insulation layer is made of environmentally friendly polyolefin material.
[0095] A method for preparing an environmentally friendly anti-interference control cable comprises the following steps:
[0096] (1) High-conductivity copper wires are twisted to form a conductor, the diameter of the conductor being 80 nm;
[0097] (2) Extruding an environmentally friendly polyolefin material on the outside of the conductor to form an insulation layer with a thickness of 1 mm;
[0098] (3) Weave tinned copper wire outside the insulation layer to form a shielding layer with a thickness of 0.8 mm;
[0099] (4) Extruding a polyvinyl chloride composition outside the shielding layer to form an outer protective layer with a thickness of 2 mm;
[0100] The preparation method of a polyvinyl chloride composition comprises the following steps: uniformly mixing polyvinyl chloride, polypropylene, stearic acid monoglyceride, nitrile rubber, modified glass fiber, propylene glycol adipate polyester, modified perlite powder, magnesium oxide, calcium zinc stabilizer, stearic acid, an antioxidant, and a plasticizer at a temperature of 85° C. to obtain the polyvinyl chloride composition.
[0101] The extrusion was performed by an extruder, and the operating parameters of the extruder were: extrusion temperature of 400° C., screw speed of 30 r / min, and pulling speed of 120 m / min.
[0102] The modified glass fiber was prepared according to Preparation Example 1-1, and the modified pearlite powder was prepared according to Preparation Example 2-1.
[0103] Example 2
[0104] An environmentally friendly anti-interference control cable, which differs from Example 1 in that the polyvinyl chloride composition includes the following raw materials, by weight: 30 kg of polyvinyl chloride, 25 kg of polypropylene, 2 kg of stearic acid monoglyceride, 10 kg of nitrile rubber, 22 kg of modified glass fiber, 6 kg of propylene glycol adipate polyester, 22 kg of modified perlite powder, 4 kg of magnesium oxide, 3 kg of calcium zinc stabilizer, 8 kg of stearic acid, 3 kg of antioxidant 1076, and 2 kg of plasticizer.
[0105] Example 3
[0106] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified glass fiber adopts Preparation Example 1-2.
[0107] Example 4
[0108] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified glass fiber adopts Preparation Example 1-3.
[0109] Example 5
[0110] An environmentally friendly anti-interference control cable is disclosed, which differs from Example 1 in that the modified glass fiber adopts Preparation Examples 1-4.
[0111] Example 6
[0112] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified glass fiber adopts Preparation Example 1-5.
[0113] Example 7
[0114] An environmentally friendly anti-interference control cable is disclosed, which differs from Example 1 in that the modified glass fiber adopts Preparation Example 1-6.
[0115] Example 8
[0116] An environmentally friendly anti-interference control cable is disclosed, which differs from Example 1 in that the modified glass fiber adopts Preparation Example 1-7.
[0117] Example 9
[0118] An environmentally friendly anti-interference control cable is disclosed, which differs from Example 1 in that the modified glass fiber adopts Preparation Example 1-8.
[0119] Example 10
[0120] An environmentally friendly anti-interference control cable is disclosed, which differs from Example 1 in that the modified glass fiber adopts Preparation Example 1-9.
[0121] Example 11
[0122] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified perlite powder adopts Preparation Example 2-2.
[0123] Example 12
[0124] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified perlite powder adopts Preparation Example 2-3.
[0125] Example 13
[0126] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified perlite powder adopts Preparation Example 2-4.
[0127] Example 14
[0128] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified perlite powder adopts Preparation Example 2-5.
[0129] Example 15
[0130] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified perlite powder adopts Preparation Example 2-6.
[0131] Example 16
[0132] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified perlite powder adopts Preparation Example 2-7.
[0133] Comparative Example
[0134] Comparative Example 1
[0135] An environmentally friendly anti-interference control cable, which differs from Example 1 in that modified glass fiber is not added.
[0136] Comparative Example 2
[0137] An environmentally friendly anti-interference control cable is different from Example 1 in that the modified glass fiber is replaced by an equal amount of glass fiber.
[0138] Comparative Example 3
[0139] An environmentally friendly anti-interference control cable is different from Example 1 in that modified perlite powder is not added.
[0140] Comparative Example 4
[0141] An environmentally friendly anti-interference control cable is different from Example 1 in that modified perlite powder is replaced by an equal amount of perlite powder.
[0142] Performance testing
[0143] The environmentally friendly anti-interference control cables prepared in Examples 1-16 and Comparative Examples 1-4 were subjected to performance tests.
[0144] Mechanical properties test: tensile strength and elongation at break were tested in accordance with GB / T 2951-2008 standard;
[0145] Heat aging resistance: expressed by the tensile strength retention rate of the cable sheath material after aging at 120°C for 240 hours;
[0146] Wear performance test: The national standard GB / T3960-2016 "Test method for sliding friction and wear of plastics" is used for testing. The lower the wear rate, the better the wear resistance. Three parallel samples are set for each group, and the average value is taken;
[0147] Normal temperature impact strength test: The normal temperature impact strength was tested according to GB / T13525-1992 standard. The test results are shown in Table 1.
[0148] Table 1 Test data of embodiments and comparative examples
[0149]
[0150]
[0151] Combining the examples and the data in Table 1, it can be seen that the environmentally friendly anti-interference control cables prepared in Examples 1-2 have good mechanical properties, impact resistance and wear resistance. Among them, the tensile strength of Example 1 is 42.6 MPa, the elongation at break is 523%, the heat aging resistance is 99%, the wear rate is 0.06%, and the room temperature impact strength is 73.8 Kj / m 2 It shows that the various components of the present application cooperate with each other, and the obtained cable sheath has excellent mechanical properties, wear resistance and durability, which prolongs the service life of the cable jacket.
[0152] In the preparation method of the modified glass fiber of Example 3, nano-silica is not added; in the preparation method of the modified glass fiber of Example 4, modified chitosan is not added; and in Examples 5-6, the mass ratio of glass fiber, nano-silica and modified chitosan is changed. As can be seen from Table 1, the tensile strength, elongation at break, heat aging resistance, wear rate and room temperature impact strength of Examples 3-4 are all worse than those of Examples 1-2; the tensile strength, elongation at break, heat aging resistance, wear rate and room temperature impact strength of Example 6 are better than those of Examples 3-4, but worse than those of Examples 1-2, indicating that nano-silica can be loaded on the surface and pores of the glass fiber, thereby increasing the strength, stiffness and impact resistance of the glass fiber, and improving the wear resistance and scratch resistance of the glass fiber. The modified chitosan makes the nano-silica and the glass fiber adhere tightly, thereby improving the mechanical properties and wear resistance of the glass fiber, and is subsequently applied to cables to improve the comprehensive performance of the cables.
[0153] In the preparation methods of the modified chitosan in Examples 7-8, nano-calcium carbonate and gum arabic were not added respectively. In Examples 9-10, the mass ratio of chitosan, nano-calcium carbonate and gum arabic was changed. As can be seen from Table 1, the tensile strength, elongation at break, heat aging resistance, wear rate, and room temperature impact strength of Examples 7-8 were better than those of Example 4. The tensile strength, elongation at break, heat aging resistance, wear rate, and room temperature impact strength of Example 10 were better than those of Examples 7-8, indicating that the nano-calcium carbonate was dispersed in the chitosan system, which improved the mechanical strength and toughness of the chitosan system. The gum arabic and chitosan were cross-linked by relying on non-covalent interactions between molecules, which improved the biocompatibility, stability and viscosity of the chitosan, and subsequently improved the performance of the glass fiber mixed with other components.
[0154] In the preparation method of the modified perlite powder in Example 11, no metal organic framework material is added. In the preparation method of the modified perlite powder in Example 12, no modified carboxymethyl cellulose is added. In Examples 13-14, the mass ratio of perlite, metal organic framework material, and modified carboxymethyl cellulose is changed. As can be seen from Table 1, the tensile strength, elongation at break, heat aging resistance, wear rate, and room temperature impact strength of Examples 11-12 are all worse than those of Examples 1-2. The tensile strength, elongation at break, heat aging resistance, wear rate, and room temperature impact strength of Example 14 are better than those of Examples 11-12, but worse than those of Examples 1-2, indicating that the metal organic framework material has good mechanical properties and can be loaded on the surface and pores of the perlite, thereby increasing the mechanical properties and wear resistance of the perlite. The modified carboxymethyl cellulose has a certain viscosity, which enables the metal organic framework material to adhere to the surface and pores of the perlite, so that the modified perlite has good mechanical properties and wear resistance, and is subsequently applied to cables to improve the corresponding performance of the cables.
[0155] In the preparation methods of the modified carboxymethyl celluloses of Examples 15-16, acrylic acid and Tween-80 were not added. As shown in Table 1, the tensile strength, elongation at break, heat aging resistance, abrasion rate, and room-temperature impact strength of Examples 15-16 were all superior to those of Example 12, indicating that acrylic acid has good film-forming, adhesive, and dispersing properties, and Tween-80 improves the emulsification and dispersibility of the system, resulting in better viscosity of the carboxymethyl cellulose system, which helps to subsequently improve the corresponding properties of the perlite.
[0156] Comparative Example 1 and Comparative Example 3 do not add modified glass fiber and modified perlite powder, respectively. As can be seen from Table 1, the tensile strength, elongation at break, heat aging resistance, wear rate, and room temperature impact strength performance are all worse than those of Examples 1-2, indicating that the modified glass fiber has extremely high strength, heat resistance, and corrosion resistance. It is added to the sheath of the cable to improve the mechanical strength of the cable; the modified perlite powder can also be loaded on the surface and pores of the modified glass fiber, thereby increasing the strength and toughness of the modified glass fiber. The corresponding performance of the subsequent added outer sheath is shown in Comparative Example 2 and Comparative Example 4, in which the modified glass fiber is replaced by an equal amount of glass fiber and the modified perlite powder is replaced by an equal amount of perlite powder, respectively. As can be seen from Table 1, the tensile strength, elongation at break, heat aging resistance, wear rate, and room temperature impact strength performance are all worse than those of Examples 1-2, but better than those of Comparative Example 1 and Comparative Example 3, indicating that the modified perlite powder and glass fiber of the present application have good mechanical properties and wear resistance, which contributes to the improvement of subsequent cable performance.
[0157] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. An environmentally friendly anti-interference control cable, comprising a conductor, an insulation layer, a shielding layer and an outer sheath, characterized in that: The shielding layer is woven from tinned copper wires, and the outer sheath is made of a polyvinyl chloride composition. The polyvinyl chloride composition comprises the following raw materials, calculated by weight: 30-36 parts of polyvinyl chloride, 20-25 parts of polypropylene, 1-2 parts of stearic acid monoglyceride, 10-13 parts of nitrile rubber, 22-25 parts of modified glass fiber, 4-6 parts of propylene glycol adipate polyester, 18-22 parts of modified perlite powder, 2-4 parts of magnesium oxide, 1-3 parts of calcium zinc stabilizer, 4-8 parts of stearic acid, 2-3 parts of antioxidant, and 1-2 parts of plasticizer. The preparation method of the modified glass fiber comprises the following steps: (1) Place the glass fiber in hydrogen peroxide, soak for 10-15 minutes, wash with water, then disperse in deionized water, add polyethyleneimine, stir for 30-35 minutes, filter and dry to obtain pretreated glass fiber; (2) Dispersing nano-silica in deionized water, adding sodium hydroxide, stirring for 1-1.5 hours, filtering, and drying to obtain pretreated nano-silica; (3) Dispersing the pretreated glass fiber of step (1) in deionized water, adding the pretreated nano-silica and modified chitosan of step (2), stirring at a temperature of 80-85°C for 1-2 hours, filtering, and drying to obtain modified glass fiber.
2. The environmentally friendly anti-interference control cable according to claim 1, characterized in that: The conductor is made of copper wire, and the insulation layer is made of environmentally friendly polyolefin material.
3. The environmentally friendly anti-interference control cable according to claim 1, characterized in that: The mass ratio of the glass fiber, nano-silicon dioxide and modified chitosan is 1:0.6-0.7:0.3-0.
4.
4. The environmentally friendly anti-interference control cable according to claim 1, characterized in that: The preparation method of the modified chitosan comprises the following steps: dispersing chitosan in deionized water, adding ammonia water, stirring evenly, washing, and drying to obtain pretreated chitosan; dispersing the pretreated chitosan in deionized water, adding nano-calcium carbonate and gum arabic, stirring at a temperature of 90-95° C. for 1-2 hours, and drying to obtain the modified chitosan.
5. The environmentally friendly anti-interference control cable according to claim 4, characterized in that: The mass ratio of the chitosan, nano-calcium carbonate and gum arabic is 1:0.2-0.4:0.08-0.
09.
6. The environmentally friendly anti-interference control cable according to claim 1, characterized in that: The preparation method of the modified pearlite powder comprises the following steps: (1) crushing the perlite, dispersing it in a sodium hydroxide solution, washing it with water, and then dispersing it in deionized water. Adding nonylphenol polyoxyethylene ether, stirring it evenly, filtering it, and drying it to obtain pretreated perlite; (2) dispersing the metal organic framework material in hydrochloric acid, stirring evenly, washing with water, and then dispersing it in deionized water, adding modified carboxymethyl cellulose, stirring evenly, filtering, and drying to obtain a pretreated metal organic framework material; (3) The perlite pretreated in step (1) is dispersed in deionized water, and the metal organic framework material pretreated in step (2) is added, stirred at a temperature of 70-75°C for 2-3 hours, and dried to obtain modified perlite powder.
7. The environmentally friendly anti-interference control cable according to claim 6, characterized in that: The mass ratio of the perlite, the metal organic framework material and the modified carboxymethyl cellulose is 1:0.6-0.8:0.3-0.
5.
8. The environmentally friendly anti-interference control cable according to claim 6, characterized in that: The preparation method of the modified carboxymethyl cellulose comprises the following steps: dispersing carboxymethyl cellulose and acrylic acid in deionized water, stirring at a temperature of 70-75° C. for 5-8 minutes, adding Tween-80, stirring for 1-2 hours, and standing to obtain the modified carboxymethyl cellulose.
9. The method for preparing an environmentally friendly anti-interference control cable according to claim 1, characterized in that: The steps include: (1) Twisting high-conductivity copper wires to form conductors; (2) Extruding environmentally friendly polyolefin material on the outside of the conductor to form an insulating layer; (3) Weave tinned copper wire outside the insulation layer to form a shielding layer; (4) Extruding a polyvinyl chloride composition outside the shielding layer to form an outer protective layer; The preparation method of the polyvinyl chloride composition comprises the following steps: uniformly mixing polyvinyl chloride, polypropylene, stearic acid monoglyceride, nitrile rubber, modified glass fiber, propylene glycol adipate polyester, modified perlite powder, magnesium oxide, calcium zinc stabilizer, stearic acid, antioxidant, and plasticizer at a temperature of 80-85° C. to obtain the polyvinyl chloride composition.
Citation Information
Patent Citations
PVC (poly vinyl chloride) insulation shielding PVC sheathed flexible cable
CN102881363A
Insulated wire with insulated rubber layer
CN108102227A